The influence of Ghana’s national culture on latent entrepreneurs: An application of Social Rule System Theory - Ansah, Martin Owusu; Chinomona, Richard (Journal of Economics and Behavioral Studies, 2017)
The impact of Ghana’s national culture on its latent entrepreneurial activities are in frequently studied on - as compare to social, economic and financial influences. The current studyexamined the impact of Ghana’s national culture on its latent entrepreneurs amongSmall and Medium Sized Enterprises (SMEs) from the view point of Social Rule System theory. The study employeda simple random sampling technique ineliciting251 respondents from the Business city of Kumasi in Ghana.It employedStructural Equation Modelling statistical technique (SEM) using Amos software version 22 in analysing the data. The results showed that, masculine and high power distance cultures in Ghana have significant positive effects on peoples’ intention to become entrepreneurs. High uncertainty avoidance and collective cultures had positive and insignificant effects on latent entrepreneurs. Thestudy presents significant contribution to the existing academic literature on national culture and latent entrepreneurial activities. Italso brings additional step towards a fundamental means of empowering people into SMEs in any developing country. Recommendationsare also providedfor useful suggestionstogovernment and policy makers in Africa towards the improvement of Small and Medium Sized Enterprises.